Dual band antenna design using stacked series array for Ka-band application - Islam, Md. Rafiqul; Nibir, Rauful; Mukit, Naimul; S. O., Abdinasir; Habaebi, Mohamed Hadi; Mohamad, Sarah Yasmin (IEEE, 2018)
In this paper, a dual band stack series array antenna is designed for the future 28 GHz Ka-band application. Dual-layer substrate Technology is used to achieve multiple resonant frequencies with higher bandwidths. Antenna is designed based on stack array of double layer with patches and resonators in different layers. Designed dual-band antennas can resonate at single band of (28 GHz) and dual band (28 and 30 GHz). All results of the simulation are fabricated and tested. The test result shows that the antennas have high gain, wide bandwidth and higher efficiencies. Both the proposed antenna configurations have shown a good candidate for 5G millimetre wave (mmWave) application.